2017
DOI: 10.1039/c7dt02903a
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, crystal structures, DFT calculations, protein interaction and anticancer activities of water soluble dipicolinic acid-imidazole based oxidovanadium(iv) complexes

Abstract: Three novel water soluble neutral mononuclear oxidovanadium(iv) complexes 1-3, [VOLB] (where HL = dipicolinic acid (DPA) and B = imidazole (1)/1-methylimidazole (2)/1-allylimidazole (3)), were synthesized by the reaction of [VOL(HO)] with imidazole/1-methylimidazole/1-allylimidazole in ethanol. The complexes were thoroughly characterized by elemental analysis, IR, UV-Vis and EPR spectroscopy, magnetic susceptibility, cyclic voltammetry and single crystal X-ray diffraction techniques. In all the complexes the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 78 publications
1
23
0
Order By: Relevance
“…Therefore, our results suggest that T1 exerts cytotoxic effects via a number of molecular mechanisms. Interestingly, Biswal et al [61] observed chromatin condensation and similar nuclear changes in Hep3B cells after treatment with vanadium complex. Importantly, we did not observe a significant increase of LDH release in cancer cells treated with T1 complexes after 48 h or 72 h, which suggests that necrosis is not induced by T1 [36].…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, our results suggest that T1 exerts cytotoxic effects via a number of molecular mechanisms. Interestingly, Biswal et al [61] observed chromatin condensation and similar nuclear changes in Hep3B cells after treatment with vanadium complex. Importantly, we did not observe a significant increase of LDH release in cancer cells treated with T1 complexes after 48 h or 72 h, which suggests that necrosis is not induced by T1 [36].…”
Section: Discussionmentioning
confidence: 92%
“…In this text, we describe the synthesis of an interesting vanadium complex by a simple solvothermal reaction. The central vanadium atom adopts a '4 + 1 + 1' geometry formed by three N atoms from1-eIM, two bridging oxygen O b from sulfate and one terminal oxygen Ot with the V-O and V-N bonds within the range of 1.597-2.186 Å and 2.082-2.125 Å, respectively [11]. The sulfate ligand is coordinated in a chelating bidentate mode with the S-O bonds within 1.448-1.518 Å.…”
Section: Commentmentioning
confidence: 99%
“…Vanadium complexes (vanadocene dichloride, Cp 2 V IV Cl 2 ) were first studied for their anticancer activity in the treatment of Ehrlich ascites tumor in the 1983. Later on Metvan, [V IV O­(4,7-Me 2 phen) 2 (SO 4 )] (4,7-Me 2 phen = 4,7-dimethyl-1,10-phenanthroline), was reported to be a promising anticancer drug against various cancer cell lines, including cisplatin-resistant testicular and ovarian cancer . Gradually, a great deal of attention has been paid toward the study of anticancer activities of several oxidovanadium complexes having O- and N-donor ligands and their underlying molecular and biochemical mechanisms, such as the (i) species or form of the complex in which they are delivered to the target organs, as the ligand-exchange and redox chemistry of vanadium complexes under biologically relevant conditions is generally complicated, (ii) regulation of metabolic pathways such as the disruption of cellular metabolism and alterations of some cellular signal transduction pathways, (iii) the mechanism of action and binding to biomolecules, and (iv) the chemical nature of the ligands that may confer better selectivity and potency to the biological efficacy of the vanadium complexes. Even our group has contributed various oxovanadium­(V/IV) complexes bearing ONO donor ligands with substantial anticancer activity against various human cancer cells. …”
Section: Introductionmentioning
confidence: 99%